Efficacy of Prostatic Specific Antigen as a Diagnostic Marker in Polycystic Ovary Syndrome and its Correlation with Lipid Profile - Aseel Rifat (Al-Anbar Medical Journal)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting a significant proportion of women and can lead to amenorrhea and infertility. High levels of prostatic specific antigen (PSA) were observed in PCOS, however, there is insufficient evidence regarding its efficacy as a diagnostic marker for this condition.Objective: To evaluate the efficacy of PSA in the diagnosis of PCOS and to assess its relation with abnormal lipid profile observed in this syndrome.Materials and methods: A case-control study including 60 patients with PCOS and 60 healthy women as a control group. Demographic data, including age and body mass index (BMI), were collected. Blood samples were obtained from each participant to measure PSA levels and lipid profile parameters. The association of PSA with lipid profile parameters was made.Results: PCOS patients had a significantly higher BMI compared to normal controls. The mean serum level of PSA in PCOS patients was significantly elevated in comparison to the control group. The cut-off value of PSA at ≥ 0.025 ng/ml was observed to be a diagnostic marker for PCOS. The highest percentage of PCOS patients were obese, with a BMI ≥ 30 kg/m2. On the contrary, most women in the control group had a normal weight. Obese women in the PCOS and control groups had significantly higher mean serum PSA levels in comparison to those who were normal or overweight. A non-significant correlation was observed between PSA levels and BMI in patients with PCOS. The mean serum levels of cholesterol (CHO), triglyceride (TG), low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL) were significantly higher in PCOS patients than in controls. In contrast, the mean high-density lipoprotein (HDL) level was significantly lower in PCOS in comparison to control. A significant positive correlation was observed for PSA with the lipid profile parameters (CHO, TG, LDL, VLDL) in PCOS patients.Conclusion: Elevated PSA levels in PCOS patients, closely linked with an abnormal lipid profile, indicate its efficacy as a potential marker for the diagnosis and monitoring of the condition.